Concept and Implementation Social Return on Investment (SROI): Case Study on MSME Culinary Redesign Program - Erwin Saraswati; Erlina Diamastuti; Arum Prastiwi; Ayu Aryista Dewi (Indonesian Journal of Sustainability Accounting and Management, 2024)
This research aims to review the Social Return on Investment (SROI) concept and analyze Corporate Social Responsibility (CSR) activities conducted by a State-Owned Enterprises (SOEs), namely PT Semen Indonesia. This research uses the survey method which employs a questionnaire, along with a literature review, focus group discussions, and interviews. This study analyzes the impact from the point of view of the stakeholders (the community and other affected parties). The result of the SROI calculation shows that the CSR program conducted by PT Semen Indonesia has resulted in a positive, significant, and substantial impact on the stakeholders. SROI ratio for CSR program is calculated at 3,46. It means that for every 1 rupiah spent, the social return on investment gained 3,46 rupiah. The CSR Program increased sales, reduced gasoline costs (economics), reduced carbon emissions (environment), and increased SME owners as well as consumers happiness (social). The stakeholders are aware of the benefits of social investment, which supports the theory of change. The limitation of this research is the complexity of calculating SROI, especially monetizing the social benefits and the social costs, which relies upon several assumptions.